Nursing mothers: Adverse events following immunization and its implication for counselling - Kikelomo O. Adubi; Bolanle M. Oyundoyin; Adijat M. Ariyo; R. A. Adekunbi; Abolanle O. Lasode (Northern Negros State College of Science and Technology (NONESCOST), 2023)
Vaccines approved for routine childhood immunization are safe and effective but sometimes there are Adverse Events Following Immunization (AEFI) which often result in ill health, various forms of deformities when it is wrongly administered and eventually forfeiture of public trust in immunization programmes. This study examined Nursing Mothers: Adverse Events Following Immunization and its Implication for Counselling. A multistage sampling procedure was used to choose 300 nursing mothers. Data were collected with the aid of a questionnaire and analyzed using means, frequency counts, percentages, Chi-square, and Pearson Product Moment Correlation (PPMC). Results revealed that the mean age of the respondents was 30 years. Pain or swelling at the injection site (85.7%) was the major existing AEFI. The majority (80.7%) of the respondents were highly knowledgeable about AEFI, while 74.0% had a negative attitude to the incidence of AEFI. The majority (68.7%) had unfavourable perception on the continuation of immunization for their children after an AEFI. The major counselling services available for nursing mothers were adherence to immunization schedules as advised by health counsellors (Mean= 2.67) and pre-counselling for nursing mothers on AEFI before child immunization (Mean =2.63). Correlation results showed that order of birth (r= 0.12), counselling services (r =0.15); awareness of nursing mothers on immunization (r=0.29) had significant relationships (p<0.05) with knowledge of nursing mothers on the AEFI. Also, respondents had high knowledge, negative attitude, and unfavorable perception to the incidence and continuation of immunization for Children after AEFI. In conclusion, order of birth, counselling services, and awareness of nursing mothers on immunization are crucial in shaping nursing mothers' knowledge on the AEFI. Hence, it was recommended that the Ministry of Health both should facilitate frequent counselling and immunization refresher courses for health counsellors on vaccine safety and how to control AEFI among nursing mothers.